Advantages of pyruvate over lactate in peritoneal dialysis solutions - Zhou Fang-Qiang (Acta Pharmacologica Sinica, 2016)
This review discusses effects of both lactate and pyruvate, and high glucose in peritoneal dialysis solutions (PDS) on leukocytes, mainly on intracellular pH ([pH](i)), glucose metabolic pathways, and apoptosis. Lactate-based PDS (L-PDS) are bioincompatible primarily due to the low pH, high lactate, and glucose excess in both individual and combination. High lactate in an acidi milieu would induce severe intracellular acidosis of leukocytes, and high glucose may disturb glucose metabolic pathways and activate protein kinase C (PKC) and nuclear factor-kappa B (NF-kappaB) of the cells, leading to apoptosis. Pyruvate-based PDS (P-PDS) are novel experimental PDS. Evidence shows that P-PDS are superior in biocompatibility. Pyruvate protection of cells has been confirmed in many fields besides the PDS area. Although the underlying mechanism whereby P-PDS preserve cell function is not fully understood, it may be associated with the maintenance of [pH](i) close to physiological, due to its low buffering capacity, improvement of cellular glucose metabolic pathways and redox state, and sustainment of intracellular calcium ([Ca2+]i) homeostasis in high glucose concentrations. It may also inhibit PKC and NF-kappaB activation in high glucose. In addition, pyruvate is a strong antioxidant, a scavenger of hydrogen peroxide (H2O2). However, exogenous pyruvate in PDS could not be an energy source for cells and also the Crabtree effect might not occur in neutrophils. Pyruvate is a hopeful candidate of buffers in PDS in the near future. Further observation of P-PDS is strongly needed with peritoneal cells to verify the cell protection both in vitro and in vivo before clinic trials.